Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nu13092914
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Rats Have Different Physiological Response to High-Fat High-Sucrose Diet but Similar Myocardial Sensitivity to Ischemia-Reperfusion Injury

Abstract: Prediabetes is a strong predictor of type 2 diabetes and its associated cardiovascular complications, but few studies explore sexual dimorphism in this context. Here, we aim to determine whether sex influences physiological response to high-fat high-sucrose diet (HFS) and myocardial tolerance to ischemia-reperfusion injury. Male and female Wistar rats were subjected to standard (CTRL) or HFS diet for 5 months. Then, ex-vivo experiments on isolated perfused heart model were performed to evaluate tolerance to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The treatment time was adjusted to 10 weeks, derived from the fact that as indicated above, pathogenesis in females is slower due to the protective effect of estrogens [8]. The manifestations observed in the bladder coincide with problems such as cystitis [9], in which there is desquamation and a loss of umbrella cells. In the case of the CAF diet, in addition, disarray and many pyknotic nuclei were found, suggesting an increase in cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment time was adjusted to 10 weeks, derived from the fact that as indicated above, pathogenesis in females is slower due to the protective effect of estrogens [8]. The manifestations observed in the bladder coincide with problems such as cystitis [9], in which there is desquamation and a loss of umbrella cells. In the case of the CAF diet, in addition, disarray and many pyknotic nuclei were found, suggesting an increase in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a set of disorders characterized by low-grade inflammation that alters various systems and is associated with type 2 diabetes mellitus and cardiovascular disease [8]. Diet plays a crucial role in the development of MetS, with the combination of high caloric intake, poor nutrient quality, and unhealthy food choices contributing to its negative impact on overall health [9]. Considering that women are more affected by bladder diseases such as UI, it is of relevance to analyze the effect of metabolic syndrome (MS) models of diet, using a cafeteria diet (CAF) or high-fat/high-sugar diet (HF/HS), on the bladder urothelia of female rats.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, despite the HFS diet, a significant increase in BW was observed only in male rats, and female rats were resistant to enriched diets in some studies. 8,9 Bladder ischemia is one of the key factors that induces bladder function deterioration. Previous studies demonstrated that bladder capacity and the contractile responses of bladder strips were decreased in atherosclerosis-induced chronic bladder ischemic model in rats and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This diet increased leptin levels in plasma of male rats but the cholesterol level was lower compared to female rats. 159 However, diets containing high fat, carbohydrates (such as fructose and sucrose) and low proteins promote leptin resistance. 160 Mediterranean diet acts as anti‐inflammatory diet that decrease leptin levels and promote leptin sensitivity while the Western diets with high saturated fatty acids enhance leptin resistance leading to obesity and induce T2D, cardiovascular health risk and certain cancers.…”
Section: Differences In Leptin Levels Across Gendersmentioning
confidence: 99%